Intensifying human-driven heatwaves characteristics and heat related mortality over Africa - Paul Adigun; Emmanuel Owoicho Abah; Oluwaseun David Ajileye (Environmental Research: Climate, 2024)
Heatwaves in Africa are expected to increase in frequency, number, magnitude, and duration. This is significant because the health burden is only expected to worsen as heatwaves intensify. Inadequate knowledge of the climate’s impact on health in developing nations such as Africa makes safeguarding the health of vulnerable groups at risk challenging. In this study, we quantify possible roles of human activity in heatwave intensification during the historical period, and project the future risk of heat-related mortality in Africa under two Representative Concentration Pathways (RCP26) and (RCP60). Heatwaves are measured using the Excess Heat Factor (EHF); the daily minimum ( T _n ) and maximum ( T _x ) are used to compute the EHF index; by averaging T _x and T _n . Two heat factors, significance and acclimatization are combined in the EHF to quantify the total excess heat. Our results confirm the intensification of heatwaves across Africa in recent years is due anthropogenic activity (increase in greenhouse gas concentration and changes in land use). The Return event highlights the potential future escalation of heatwave conditions brought on by climate change and socioeconomic variables. RCP26 projects a substantial rise in heat-related mortality, with an increase from about 9000 mortality per year in the historical period to approximately 23 000 mortality per year at the end of the 21st century. Similarly, RCP60 showed an even more significant increase, with heat-related mortality increasing to about 43 000 annually. This study highlights the potentially growing risk of intensifying heatwaves in Africa under different emission scenarios. It projects a significant increase in heatwave magnitude, number, duration, frequency, and heat-related mortality. Africa’s low adaptive capacity will amplify the impact, emphasizing the need for emissions reduction and effective adaptation measures.